The Effectiveness of Local Wisdom-Based Project-Based Learning in Environmental Learning: A Systematic Review of PRISMA - Annisa Fitri Aulia; Achmad Ali Fikri (Universitas Islam Negeri Walisongo Semarang, 2026)
Environmental learning requires a contextual approach so that students are able to understand environmental problems in a real and meaningful way. Project Based Learning (PjBL) based on local wisdom is considered relevant because it integrates learning projects with local cultural and environmental potential. This study aims to analyze the application of PjBL based on local wisdom in environmental learning and its impact on learning outcomes and students' environmental awareness. The research method used is a Systematic Literature Review (SLR) by searching national and international journal articles published in the last ten years through Google Scholar. The results of the study indicate that PjBL based on local wisdom can improve students' critical thinking skills, creativity, problem solving, and environmental awareness. The conclusion of this study confirms that PjBL based on local wisdom is effectively applied in environmental learning and has the potential to support sustainable education.